Effects of Salinity on Tagetes Growth, Physiology, and Shelf Life of Edible Flowers Stored in Passive Modified Atmosphere Packaging or Treated With Ethanol - Chrysargyris, Antonios; Tzionis, Andreas; Xylia, Panayiota; Tzortzakis, Nikos (Frontiers in Plant Science, 2018)
Irrigation with saline water causes significant crop yield loss. However, short-term saline application might cause less negative effects on yield yet at the same time improve quality aspects of edible products. Tagetes (Tagetes patula L.) plants were subjected to salinity (0-50-100 mM NaCl) and harvested flowers were stored up to 14 d in passive modified atmosphere packaging (with or without ethanol application). Salinity of 100 mM NaCl decreased plant biomass and plant size (i.e. height) and had a negative effect on physiological processes such as stomatal closure and chlorophylls content decrease. Salinity increased flower polyphenols, antioxidant activities and total carotenoids but decreased anthocyanins, and greater impacts were found at salinity of 100 mM NaCl, providing higher antioxidant value of the edible flowers. Short-term saline exposure of tagetes plants activated metabolic processes and as a result there was an accumulation of minerals such as N, P, Na, and Zn on edible flowers. During storage, salinity maintained but ethanol application increased the flower CO2 production. Ethanol application decreased the decay of flowers subjected to 100 mM NaCl. Flower weight losses and marketability accelerated at salinity of 100 mM NaCl after 14 d of storage. Tagetes flowers demonstrated induction in both non-enzymatic (i.e. proline content) and enzymatic mechanisms (catalase) to overcome stress caused by salinity during harvest stage and/or ethanol at storage. Our results have shown that short-term exposure to salinity and/or ethanol is able to achieve higher carotenoids and anthocyanins levels and these compounds can be considered as a new source of nutraceuticals.